Rise of the (possible) resistance: a review of susceptibility patterns for nontyphoidal Salmonella enterica in Nebraska - Shawnalyn W. Sunagawa; Catherine Christopherson; Scott J. Bergman; Molly M. Miller; Mackenzie R. Keintz; Taylor A. Wahlig; Paul Fey; Trevor C. Van Schooneveld (Cambridge University Press, 2023)
Our institution sought to evaluate our antimicrobial stewardship empiric treatment recommendations for Salmonella. Results from 36 isolates demonstrated reduced susceptibilities to fluoroquinolones with 1 isolate susceptible only to ceftriaxone. Analysis supports the current recommendation of empiric ceftriaxone therapy for severe infection and updated recommendation for sulfamethoxazole-trimethoprim in non-severe infections.